An Evaluation to Establish the Acceptable Serum Triglyceride Levels in Neonates Receiving Intravenous Fat Emulsion Infusion in a Multicenter Retrospective Study - Chan, Belinda; Lian, Anh; Baer, Vickie; Robinson, Mandy; Ou, Zhining; Presson, Angela P.; Zinkhan, Erin K. (American Journal of Perinatology, 2020)
Objective This study aimed to establish neonatal serum triglyceride (TG) level reference ranges during lipid infusion and correlate peak TG with neonatal outcomes.Study Design This is a retrospective review of 356 neonates with 696 TG measures obtained in four neonatal intensive care units between 2015 and 2017. TG was evaluated collectively to establish a reference range and a threshold limit. To analyze the effects of a higher TG threshold, neonates were categorized by their peak TG: <180 (TG<180), 180 to 400 (TG180–400), and > 400 mg/dL (TG>400). Univariable and multivariable regression models were constructed to compare peak TG to patient characteristic and clinical outcomes.Results The frequency of TG > 400 mg/dL was 5% and found only in neonates weighing < 1.5 kg. Neonates in the TG180–400 (n = 91) group were significantly lower in birth weight and gestational age, had lower 5-minute APGAR scores, and had increased ventilatory requirement when compared with neonates in the TG<180 (n = 240) group (all p < 0.001). The TG180–400 group had increased risk of severe intraventricular hemorrhage (p = 0.02) and bronchopulmonary dysplasia (p = 0.03). Elevated TG was associated with mortality (odds ratio [OR]: 14.4, p < 0.001) in univariable analysis, but the relationship weakened (OR: 4.4, p = 0.05) after adjusting for comorbidities in multivariable logistic regression.Conclusion It is unclear if the adverse outcomes seen in neonates with higher peak TG were due to elevated TG alone, or whether illness severity predicted the increased TG. More prospective studies are needed to further delineate the relationships.
Keywords: triglyceride; intravenous fat emulsion infusion; Intralipid; fatty acids; total parenteral nutrition; neonate; preterm; infants